A novel spectral beam splitting photovoltaic/thermal hybrid system based on semi-transparent solar cell with serrated groove structure for co-generation of electricity and high-grade thermal energy. (15th January 2022) - Liang, Huaxu; Su, Ronghua; Huang, Weiming; Cheng, Ziming; Wang, Fuqiang; Huang, Gan; Yang, Dongling
Graphical abstract: Semi-transparent solar-cell-based SBS PV/T system is promising. However, traditional semi-transparent solar cell-based SBS PV/T system can only produce low-grade thermal energy because the semi-transparent solar cell cannot concentrate long-wavelength sunlight. Even if a concentrating system is used, the semi-transparent solar cell must be able to withstand high temperatures, which increases the costs of the solar cell, and an additional bracket is required for installing the concentrator. In this study, the idea of using a single piece of photovoltaic (PV) to regulate the radiative transfer of the full solar spectrum for realizing the co-generation of electricity and high-grade thermal energy is proposed. A semi-transparent solar cell with a serrated groove structure at its bottom was fabricated. The solar cell can convert 400–800 nm wavelength photons to electricity, and focus 800–2500 nm wavelength photons on a small spot to produce high-temperature thermal energy. Therefore, the transmitted irradiance can be improved with a simple structure in a semi-transparent solar cell-based SBS PV/T system. Highlights: Semi-transparent solar cell with serrated groove structure for SBS is proposed. Idea of using a single piece of PV to regulate full solar spectrum is proposed. Semi-transparent solar cell-based SBS PV/CST system is experimentally studied. Feasibility of such novel system is validated by indoor and outdoor experiments. The utilization efficiency of the full-spectrum solar energy can reach 77%. Abstract: Semi-transparent solar cells can be used for spectral beam splitting (SBS) in which short-wavelength photons are converted to electricity and long-wavelength photons are transmitted to thermal absorbers. However, these thermal absorbers can only produce low-grade thermal energy because the semi-transparent solar cell cannot concentrate long-wavelength photons. In this study, based on the idea of regulating the radiation field to match the energy conversion on-demand, the strategy to use a single piece of photovoltaic (PV) to regulate the photon capture of the full solar spectrum for realizing the co-generation of electricity and high-grade thermal energy is proposed. A semi-transparent solar cell with a serrated groove structure at the bottom is designed and fabricated. The cell can convert 400–800 nm wavelength photons to electricity, and focus 800–2500 nm wavelength photons to a small spot to produce high-temperature thermal energy. A novel α-Si thin-film semi-transparent solar cell-based SBS hybrid photovoltaic/concentrated solar thermal system is established. The feasibility of the system is validated through indoor and outdoor experiments. The utilization efficiency of the full-spectrum solar energy can reach 77%. The high average concentrated irradiance of up to 4.31 KW/m 2 transmitted through the semi-transparent solar cells is sufficient for high-temperature thermal utilization.